Structural assessment of damaged and CFRP repaired reinforced concrete beams from experimental modal analysis / Moatasem Mohammed Fayyadh - Moatasem, Mohammed Fayyadh (2012)
Many engineering structures suffer damage and deterioration with time, and need to be monitored in order to sense and predict risk of failure during its remaining service life. Damaged structures require repair work to be undertaken in order to prevent further loss of structural integrity and externally bonded Carbon Fibre Reinforced Polymer (CFRP) is one of the most widely used repair technique. In order to assess the damage and ascertain the appropriateness and effectiveness of the repaired system, various tests can be conducted on the structural element concerned. In this study, experimental modal analysis was conducted on undamaged, load induced damaged and CFRP repaired reinforced concrete beams. A total of sixteen reinforced concrete beams were cast and categorised into three groups with different loading conditions. The first group of beams were tested under a concentrated point load at mid-span to induce flexural damage while the remaining two groups for shear damage with loading positions at quarter span and close to the support. Previous studies have used modal parameters for damage detection and the assessment of repair work, and showed that existing algorithms used for damage detection sometimes produced inaccuracies and anomalies. Thus in this study, new algorithms based on natural frequencies and mode shapes for damage detection are proposed to overcome some of the shortcomings which are related to reinforced concrete (RC) being a composite and heterogeneous material. Furthermore, the effectiveness of the CFRP sheets as flexural and shear repair system was assessed based on modal data extracted from the tests. The results showed there was evidence of the influence of the RC composite action on the natural frequencies. By utilising the proposed algorithms in the form of damage detection indices, the type and cause of damage were identified and gave better sensitivity with regards to damage severity. Furthermore it was also apparent that the indices were sufficiently reliable in assessing the effectiveness of the CFRP repair for both flexural and shear damage. The failure modes obtained from the CFRP repaired beams were identified as debonding when subjected to flexure, combination of flexural cracks and CFRP delamination together with a concrete layer for shear at quarter-span and a combination of shear and CFRP debonding for shear close to the support. Based on the results of this study, changes to the existing ACI equations for design of CFRP repaired beams under flexure and shear were proposed. These included modified equations for concrete and shear stirrups contribution, contribution of the external CFRP sheets and the contribution of the flexural steel. The predicted loads based on the modified form gave better agreement with the experimental results from this study.